The ethylene receptor mutation etr2b reveals crosstalk between ethylene and ABA in the control of Cucurbita pepo germination. Issue 1 (10th February 2023) - Iglesias‐Moya, Jessica; Cebrián, Gustavo; Garrido, Dolores; Martínez, Cecilia; Jamilena, Manuel
Abstract: The enhanced salt tolerance of squash ethylene‐insensitive mutants during germination and early stages of seedling development suggested that abscisic acid (ABA) could mediate this tolerance. To gain insight into the crosstalk between ethylene and ABA in seed germination, the germination rate and early seedling growth of wild type (WT) and ethylene‐insensitive etr2b mutant were compared in seeds germinated under water and exogenous ABA treatment. The etr2b seeds germinated earlier than WT under both water and ABA, and the effect of ABA on radicle length and seedling growth of etr2b was lower than in WT, indicating that etr2b is also insensitive to ABA. The comparison of ABA and ethylene contents and ABA and ethylene gene expression profiles in WT and etr2b dry and imbibed seeds in either water, NaCl or ABA demonstrated a clear crosstalk between ethylene and ABA in germination. The expression profiles of ethylene genes in WT and etr2b indicated that the role of ethylene in seed germination does not appear to follow the canonical ethylene signaling pathway. Instead, etr2b reduces ABA content during formation of the seeds (dry seeds) and in response to seed imbibition and germination, which means diminished dormancy in the ethylene mutant. The etr2b mutation downregulated the expression of ABA biosynthesis and signaling genes during germination, demonstrating the positive role of ethylene receptor gene CpETR2B on seed germination and early seedling growth in squash is mediated by ABA. The reduced effect of exogenous ABA on ethylene production and ethylene gene expression in etr2b seeds suggests that this regulation is also dependent on ethylene.